2018
DOI: 10.4314/mmj.v30i3.3
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of couple antenatal education: A qualitative study of expectant couples attending antenatal clinics in Blantyre, Malawi

Abstract: BackgroundFew studies have assessed the effectiveness and acceptability of male partner involvement in antenatal education. Yet, male involvement in antenatal care including antenatal education has been proposed as a strategy to improve maternal and neonatal outcomes. We conducted this study to add to the body of knowledge on acceptability of male partner involvement in antenatal education following an intervention.MethodsThis was a cross sectional qualitative study using 18 in-depth interviews with 10 couples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The international literature also described male involvement in maternal health services, including prenatal education as a favorable strategy for fulfilling supportive roles, leading to the development of safe maternity practices, and the preparation for childbirth, and the identification, treatment, and prevention of maternal-fetal complications. ( 13 ) The paternal insertion in prenatal care promotes access to nursing consultations, meeting their demands and how to perform exams and immunization, a proposal widely recommended by the Ministry of Health, based on encouraging the implementation of male prenatal care. The political strategy called "male prenatal care" aims to encourage the father to make frequent visits to health services in a preventive manner, developing a greater emotional bond between him, his partner, and the child, and track infectious diseases, and expand access to health services.…”
Section: Discussionmentioning
confidence: 99%
“…The international literature also described male involvement in maternal health services, including prenatal education as a favorable strategy for fulfilling supportive roles, leading to the development of safe maternity practices, and the preparation for childbirth, and the identification, treatment, and prevention of maternal-fetal complications. ( 13 ) The paternal insertion in prenatal care promotes access to nursing consultations, meeting their demands and how to perform exams and immunization, a proposal widely recommended by the Ministry of Health, based on encouraging the implementation of male prenatal care. The political strategy called "male prenatal care" aims to encourage the father to make frequent visits to health services in a preventive manner, developing a greater emotional bond between him, his partner, and the child, and track infectious diseases, and expand access to health services.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to the methodologies and involvement of the support network, this is related to existing studies. An investigation carried out with a couple of pregnant women in health centers in Malawi indicated that the parents stated that the content of the sessions covered essential aspects of maternal health and both the frequency and the duration of the meetings were appropriate [12]. In Ontario, Canada, a study that evaluated the change in knowledge associated with participation in prenatal education programs found that most pregnant participants (n = 511) were satis ed with the content covered during the course [13].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested ways to involve men in antenatal care. 65,66 Interactive group couples' classes have been found to provide interaction opportunities for men from similar backgrounds and facilitate learning outside of scheduled antenatal education sessions. 65 Some men cited having relationship issues as reasons for low involvement.…”
Section: Men's Involvementmentioning
confidence: 99%